PENGEMBANGAN MOTIF BATIK TULIS DENGAN SUMBER IDE CORAK KAIN TENUN BIMA - Anindhita Destiana Nur Ifani; Theresia Widyastuti (Hastagina : Jurnal Kriya Seni, 2021)
Batik is a creative industry product that has been around for a long time and has been developed by many artisans in various regions in Indonesia. The author will use one of the traditional weaving motifs in Indonesia, namely Mbojo weaving as a source of motif ideas from written batik. The mbojo woven fabric is a form of Indonesian culture originating from the Bima Regency, West Nusa Tenggara Province (NTB) and several other areas around Mount Tambora. In its design using 5 stages of Clipson's theory. Then the author conducted an experiment, studying the meanings and symbols that exist in the Mbojo Bima woven fabric pattern, paying attention to its characteristics and also reprocessing it into the form of written batik. This design resulted in eight designs with one work being realized. The visual changes or combines two forms of traditional fabrics, namely weaving and batik, which in their depiction have a significant difference, namely batik which has relatively flexible visual lines, while weaving which has a visual appearance that looks stiff. By testing several images to form a stiff woven pattern into a batik motif whose depiction looks flexible, then also paying attention to the aspect of laying motifs and repeating motifs so that this design looks good. After that, it is realized with the written batik technique according to the size of the image that has been made.